2020
DOI: 10.1016/j.jdent.2020.103328
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of human and bovine enamel in a microbial caries model at different biofilm maturations

Abstract: Objectives: To compare human versus bovine enamel when used in microbial caries models; and to evaluate the use of nylon mesh to support biofilm growth over enamel. Methods: Twenty-four subsubgroups were included (time factor: 4, 8, and 12 days; substrate factor: human/bovine; mesh factor: yes/no; treatment factor: 18.4 mM NaF (350 ppm F), de-ionized water [DIW]; n=9/sub-subgroup).Microcosm biofilm from human saliva (IRB approval #1406440799) was grown on enamel specimens for 24-h (Brain Heart Infusion media; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Even if we consider the small decrease in color depth as a reduction of adsorbed macromolecules, no correlations between adhesion force and adsorbed amount or rupture length and adsorbed amount were found. This is probably due to the fact that variations in adhesion forces and rupture lengths are quite large between individual bacteria, depending on the study design. ,,, The data shows that small changes in the thickness of the film do not influence the adhesion process significantly.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Even if we consider the small decrease in color depth as a reduction of adsorbed macromolecules, no correlations between adhesion force and adsorbed amount or rupture length and adsorbed amount were found. This is probably due to the fact that variations in adhesion forces and rupture lengths are quite large between individual bacteria, depending on the study design. ,,, The data shows that small changes in the thickness of the film do not influence the adhesion process significantly.…”
Section: Resultsmentioning
confidence: 90%
“…This is probably due to the fact that variations in adhesion forces and rupture lengths are quite large between individual bacteria, depending on the study design. 17,40,61,49 The data shows that small changes in the thickness of the film do not influence the adhesion process significantly. Sample Characterization.…”
Section: ■ Materials and Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, it has been observed that the use of this substrate in the microbial caries model showed similar behavior to human teeth. 31 To suspend or minimize the structural loss in high-risk caries, an experimental chitosan/casein treatment was employed, as literature has shown that casein, a milk protein, is similar in function to proteins responsible for the biomineralization of the tooth. 20,32 Casein phosphopeptide, in particular, can bind to surfaces such as plaque, soft tissue and dentin, as well as provide a reservoir of bio-available calcium and phosphate in the saliva and on the surface of dental structure.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the treatment was conducted on natural enamel surface without flattening to simulate the in vivo conditions [ 37 ]. Bovine enamel is readily available, and has found to have a close behavior to that of human enamel regarding biofilm cariogenicity and lesion severity [ 38 ]. However, bovine enamel has shown to have a higher hardness, larger crystal size, and faster rate of lesion progression (1.4:1) than those of human enamel [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%